Genetic analysis of SNPs in the MLF2 and TCR-β genes for growth traits in Korean native chickens - CHOI, SO-YOUNG; SINGH, NARESH KUMAR; YANG, SONG-YI; HONG, MIN-WOOK; JEONG, DONG KEE; LEE, KYUNGBAEK; HONG, YEONG HO; LEE, SUNG-JIN (The Indian Journal of Animal Sciences, 2018)
The myeloid leukemia factor 2 (MLF2) and T-cell receptor β (TCR-β) genes are associated the development of resistance towards coccidiosis infection. Five single-nucleotide polymorphisms (SNPs) located on these genes (SNP_892 and intron 7 (10) of MLF2 and SNP_88, 434, and 561 of TCR-β) were identified and considered to be the genetic markers for resistance to coccidiosis. In this study, we investigated the association between these SNPs and the body weight of Korean native chicken (KNC) and the possibility of using these SNPs as genetic markers for improving growth in KNCs. KNC specimens (798) were genotyped using high-resolution melting analysis, and single-marker association tests were performed; body weights of KNC were also measured every 2 weeks. Three SNPs [892 and intron 7 (10) of MLF2 and 88 of TCR-β] had significant associations with body weight in some period of growth of KNC. Further, 2 SNPs (434 and 561) of TCR-β were linked and significantly associated with the overall growth of KNCs. Conclusively, the findings of the present study suggested that SNPs in the MLF2 and TCR-β genes could be used as combinations of genetic markers for selecting high growth performance specimens of KNCs.